The Eurasian Integration as a New Stage of Development of the Russian Statehood - O. A. Podberezkina (Vestnik MGIMO-Universiteta)
In the article eurasian integration is examined from the point of view of the new stage of development of the Russian state system. To that purpose are analysed the features of «phase transition» of Russia to qualitatively new civilization essence, line of the national innovative system, structure of creative class and demographic potential of country, sixth technological mode and chances of capture its to the Russian Federation.